Analyses of the pathogen and weather components of disease progress for modeling apple scab epidemics in integrated and organic production systems - Holb, I. J. (International Journal of Horticultural Science, 2003)
The pathogen and weather components of apple scab disease progress were analysed in a three-year study, in two environmental-friendly production systems (organic and integrated) on cvs. `Idared’, `Jonica’ and ’Mutsu’. Linear regression analyses of transformed disease incidence and severity data and "area under the disease progress curves" (AUDPC) were used for the analysis of the pathogen component. To evaluate the role of the weather component in apple scab epidemic, first, the weekly disease increase was determined at a certain week (n). Weekly disease increase was related to rainfall, relative humidity, Mills’ wetness period, temperature and interaction between temperature and relative humidity. Five different periods were used in the analyses: i) week (n-1), ii) week n(n-1), iii) week (n-2), iv) week (n-1)(n-2) and v) week n(n-1)(n-2). In the analyses of the pathogen component, the best transformation function was the logistic one. Regression analyses showed that disease growth rates were higher for disease incidence and for the organic production system than for disease severity and for the integrated production system, respectively. Disease growth rates for leaf incidence were higher than fruit incidence on all the three cultivars. AUDPC values showed great differences in both leaf and fruit incidences among cultivars and between the two production systems. The results the of analyses of the weather component showed that the best relationships between disease increase and weather parameters were found for fruit incidence and leaf incidence in week (n-2) in the organic and integrated production systems, respectively. Results also demonstrated that in week n(n-1) temperature played a more important role in the fungus development than the water parameters (relative humidity, rainfall and leaf wetness). Consequently, infection process is significantly dependent on almost all weather parameters, but during the incubation period the most important weather parameter is the temperature. Results were compared with similar studies and biological interpretations of the analyses are discussed.